Possibilities and barriers for practical application of internationally recognized diplomas of remote education. Issue 3 (8th April 2019) - Tyurina, Yulia; Troyanskaya, Mariya; Ermolina, Lilia; Bogoviz, Aleksei V.; Lobova, Svetlana
Abstract : Purpose: The purpose of this paper is to determine the possibilities and barriers of the practical application of internationally recognized diplomas of higher education. Design/methodology/approach: The authors used SWOT analysis for determining preconditions and barriers as well as possibilities and threats that are related to the provision and practical application of internationally recognized diplomas of higher education and the method of modeling of socio-economic processes and systems for compiling a conceptual model of the provision and practical application of internationally recognized diplomas of higher education. Demand for the practical application of internationally recognized diplomas in modern Russia is determined with the method of analysis of statistical data (method of economic statistics). The information and analytical basis of the research consists of materials of the Federal State Statistics Service of the Russian Federation. Findings: It is shown by the example of modern Russia that the practical application of internationally recognized diplomas is popular, and universities that provide remote education possess wide possibilities in the sphere of their provision, as they are characterized by high flexibility that allows them to adapt to the international standards of university education. The barriers of the practical application of internationally recognized diplomas of higher education are caused by the lack of clear and generally recognized international standards of university education, absence of entrepreneurial culture of application of internationally recognized diplomas and absence of international organization that certifies activities of universities and issues licenses for internationally recognized diplomas. Originality/value: In order to overcome these barriers, the authors created a conceptual model of the provision and practical application of internationally recognized diplomas of higher education.